Advancements in Clustering Protocols for Wireless Sensor Networks-Assisted Internet of Things – A Comprehensive Review - A. Kalaivani, A. Kalaivani (Journal of Neonatal Surgery, 2025)
According to the current study, there will be a large number of Internet-connected systems, including not just mobile phones but also devices capable of performing a range of duties such as data collection and operation under outdoor circumstances. Accordingly, WSNs are essential to the Internet of Things (IoT) paradigm to provide several advantages, including intelligence, adaptability, and dependability. Typically, a collection of sensors with constrained power and memory resources is used to build the WSN. However, the biggest challenge in these systems is the high energy consumption during data transfer from the origin node to the destination nodes, which affects the node's lifetime. Energy consumption has become a crucial design concern in WSN-IoT systems, as it is very impossible to replace or recharge the batteries in those nodes. Therefore, in WSN-IoT systems, the clustering protocol is crucial to improving network lifetime and energy efficiency. Numerous academics have developed many clustering techniques to help WSN-IoT devices save energy. By grouping the nodes according to various parameters, such as the node's residual energy, the distance between other nodes, etc., these protocols primarily aim to maximize energy productivity. This paper provides a thorough analysis of several clustering techniques for WSN-IoT systems. Additionally, it presents those protocols' advantages, drawbacks, and simulation effectiveness in tabular form. To evaluate certain protocols in terms of network lifetime, residual energy, throughput, Packet Delivery Ratio (PDR), and stability, some of them have also been simulated. Lastly, certain possible modifications are suggested to reduce the energy consumption of WSN-IoT systems and extend their lifespan.